Assessoria jurídica popular universitária : uma alternativa na assistência jurídica - Aguiar, Anne Adelle Gonçalves de (2013)
This research built a historical path of development and conceptualization of Legal Services Popular College (AJUP) in Brazil, based on the exploitation concepts affections, to achieve a model analysis of University Extension's Innovative Legal Advice Popular as an alternative proposal in providing the social right to legal assistance. The AJUP is a movement grounded in rights education, in order to overcome the traditional concept of access to justice, as an access to the courts for a new concept that considers the justice that is beyond the law and procedures. Effective justice in the sense of social equality, since freedom and equality-fraternity gracing ideologically capitalism since its founding to the present day, not secured itself access to justice of the working class.